Pengaruh Penggunaan Presensi Berbasis Sidik Jari di Dinas Pendidikan dan Kebuayaan Muaro Jambi - Sintia, Agnes; Firman, Firman (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2024)
This study aims to determine the influence of Fingerprint-Based Attendance and Discipline on the Work Commitment of Non-Civil Servants at the Muaro Jambi Education and Culture Office. This study uses a quantitative method and research data is obtained by distributing questionnaires to non-civil servants. The population in this study is Non-Civil Servants at the Muaro Jambi Education and Culture Office. The sample in this study is 50 Non-Civil Servants with a sampling technique using the total sampling technique. The results of this study show that: (1) There is an effect of Fingerprint-Based Attendance on Work Commitment. This is evidenced by the results of the t-test with a calculated t-value greater than the t-value of the table, which is 2.705 > 2.011 with a percentage of 21.3%. Therefore, there is a significant influence between fingerprint-based attendance and employee work commitment, so H¬¬o is rejected and Ha is accepted. (2) There is an influence of work discipline on the employee's work commitment. This is evidenced by the results of the t-test witha calculated t-value greater than the t-value of the table, which is 2.472 > 2.052 with a percentage of 11.3%. Therefore, there is a significant influence between work discipline and employee work commitment, so Ho ¬is rejected and Ha is accepted. (3) There is an influence of fingerprint-based attendance and discipline on employee work commitment. This is evidenced by the results of the F test with a calculated t-value greater than the t-valueof the table¬, which is 4.653 > 3.18 with a percentage of 12.8%, the remaining 87.2% is influenced by other variables that are not discussed in this study. Therefore, there is a significant influence between fingerprint-based attendance, work discipline and employee work commitment, so H o is rejected and Ha is accepted.